Peran Komunikasi Efektif Kepala Sekolah Dalam Meningkatkan Motivasi Kerja Guru - ., Zurhidayati; Hendriani , Suswati (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The headmaster's communication style can cause misinterpretation and ambiguity in delivering messages to teachers. This type of study is qualitative research with a descriptive method. The subjects of this study were the headmaster and ten teachers of SMP Negeri 2 Sijunjung. The instrument of this study was an interview sheet, collecting data through interviews. The data collected were analyzed using a thematic approach. The results of the study findings show that the communication carried out by the headmaster to motivate teachers includes the ability to deliver messages clearly, an inclusive leadership style and focuses on community building, the role of the headmaster as a facilitator in the decision-making process, routine communication, support in overcoming problems faced by teachers, and the application of effective communication practices such as transparency, empathetic approach, building interpersonal relationships, and providing constructive feedback to teachers. In conclusion, the headmaster's communication is essential in increasing teachers' work motivation to create a positive work environment and improve the quality of education.